Cultural Element: Coffee Table Inspired by Wau Bulan In Representing the Identity of Malaysia - Asril, Nadhirah; Md Rawi, Muhammad Firdaus (Research in Management of Technology and Business, 2026)
Traditional heritage has been considered as outdated by the society caused the identity of Malaysia to fade due to the mindsets of society and today’s trend. This research investigates the combination of Wau Bulan, a traditional Malaysian kite, in the modern furniture design of the coffee table. The research aims to counter the sense that cultural heritage is by integrating Wau Bulan motifs into a minimalist style of furniture, suitable for today’s furniture style. This research method uses the quantitative survey involving 205 respondents in Setapak, Kuala Lumpur, and the results showed majority of the respondents strongly agree with integrating cultural heritage into minimalist furniture design. Other research methods are visual research and design development, which involve thumbnail sketching, ideation, idea development, and a scale-size mockup build. For the final design, it combined traditional and current design ideas to develop a coffee table that reflects both traditional values and minimalist aesthetics. The study goal is to develop an innovation of a coffee table with elements of Wau Bulan and to show the unique elements of Wau Bulan.